The Effect of 2, 4 D (Dichlorophenoxyacetic acid) and BAP (Benzyl Amino Purine) Concentration on the Establishment of Patchouli (Pogostemon cablin Benth) in Vitro - Wardani, Dwika Karima; Satria, Benni; Mayerni, Reni (International Journal of Environment, Agriculture and Biotechnology, 2019)
The aim of this study was to determine the concentration of 2,4-D growth regulator and the most effective BAP for the formation of callus for endemic patchouli plants in western markets, namely Akasesi Situak in vitro. The research has been carried out at the Andalas University Faculty of Agriculture Tissue Culture Laboratory, in September November 2018. The method used is Random Trap Design (RAL) with 2 treatment factors, namely 2,4-D (0, 0.5, 1, 1.5, and 2 mg). / l) and BAP (0, 0.5, 1, 1.5, and 2 mg / l), the total consists of 25 treatments with 3 replications with codes namely A1S1, A1S2, A1S3, A1S4, A1S5, A2S1, A2S2, A2S3, A2S4 , A2S5, A3S1, A3S2, A3S3, A3S4, A3S5, A4S1, A4S2, A4S3, A4S4, A4S5, A5S1, A5S2, A5S3, A5S4, A5S5. Data were statistically analyzed by F test at 5% real level. If F count is greater than F table 5%, then proceed with Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results of the study show that on the treatment of A3S3 (1.0 mg / l 2.4-D + 1.0 mg / l BAP), A3S4 (1.0 mg / l 2.4-D + 1.5 mg / l BAP), A3S5 (1.0 mg / l 2.4 -D + 2.0 mg / l BAP) and A4S1 (1.5 mg / l 2.4-D + without BAP) produce explants. whereas in other combination treatments up to 30 days of observation did not produce patchouli plants in the Situak Accession plant.